Transformational Leadership, Work Stress, and Employee Performance: The Mediating Role of Work Motivation in the Financing Industry - Rachmasari Nur Hutaminingtyas; Sabihaini Sabihaini; Sri Dwi Ari Ambarwati (Global Sustainability Research Institute, 2026)
Employee performance is a critical factor in determining organizational effectiveness, particularly in the financing industry, which is characterized by high performance targets and competitive work environments. This study aims to examine the effect of transformational leadership and work stress on employee performance with work motivation as a mediating variable in the financing industry. This study employed a quantitative explanatory research design using a census approach involving 70 contract employees as respondents. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that transformational leadership has a positive effect on work motivation and employee performance, while work stress has a negative effect on work motivation and employee performance. Furthermore, work motivation positively affects employee performance and significantly mediates the relationship between transformational leadership and employee performance, as well as between work stress and employee performance. This study contributes theoretically by extending the application of Self-Determination Theory (SDT), Social Exchange Theory (SET), and Job Demands-Resources (JD-R) Model in explaining the mechanism through which organizational and psychological factors influence employee performance in the financing industry. Practically, this study suggests that management should strengthen transformational leadership practices, manage work stress effectively, and enhance employee motivation to improve performance.